A TMS/EEG protocol for the causal assessment of the functions of the oscillatory brain rhythms in perceptual and cognitive processes - Trajkovic, Jelena; Di Gregorio, Francesco; Marcantoni, Eleonora; Thut, Gregor; Romei, Vincenzo (STAR protocols, 2022)
The combined use of transcranial magnetic stimulation (TMS), electroencephalogram (EEG), and behavioral performance allows investigation of causal relationships between neural markers and their functional relevance across a number of perceptual and cognitive processes. Here, we present a protocol for combining and applying these techniques on human subjects. We describe correlation approach and causal approach to disentangle the role of different oscillatory parameters, namely alpha frequency and amplitude that control for accuracy and metacognitive abilities, respectively, in a visual detection task. For complete details on the use and execution of this protocol, please refer to Di Gregorio et al. (2022). [Display omitted] •EEG-behavior correlations to frame hypotheses on how the brain shapes behavior•Combined TMS-EEG-behavior to establish causal brain-behavior relationships•Tune alpha frequency and amplitude to shape perceptual accuracy and metacognition Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics. The combined use of transcranial magnetic stimulation (TMS), electroencephalogram (EEG), and behavioral performance allows investigation of causal relationships between neural markers and their functional relevance across a number of perceptual and cognitive processes. Here, we present a protocol for combining and applying these techniques on human subjects. We describe correlation approach and causal approach to disentangle the role of different oscillatory parameters, namely alpha frequency and amplitude that control for accuracy and metacognitive abilities, respectively, in a visual detection task.